PENERAPAN PEMBELAJARAN MENGGUNAKAN PENDEKATAN SAVI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VII-C MTs NURUT TAQWA CERMEE BONDOWOSO PADA POKOK BAHASAN TINDAKAN EKONOMI MATA PELAJARAN IPS - Arico Ayani Suparto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Low student learning activities that have an impact on learning outcomes is a teacher's problem that must be addressed immediately. According to Sudjana (in Djamali, 2001: 123), "in the learning process the essence is student activity. Lesson learned activities are learned by the teaching approach used by the teacher. Therefore, the teacher in an effort to stimulate student learning activities must be able to create a conducive classroom atmosphere. Teachers must always give students enough things to think about and do. One of them is by taking a learning approach that is able to move students to carry out learning activities in the social studies learning process, namely by implementing learning using the SAVI approach. In cycle 1 the indicators involving physical activity of students have a high category, because it reaches a score of 3.3 while in student activities it has a category Also high, namely 3.08 on this indicator, all students who simulated simulations or played roles related to 36 students. Then the average in cycle 1 is 3.03. This is because students in this study are still in the stage of self-determination so that when the teacher teaches there are still many students who talk to friends. The analysis that was carried out on the results of daily tests showed that classical completeness had not been reached from 85% so that it was necessary to hold a second cycle. The results of daily tests after learning using the SAVI approach showed that students could not understand the material. This can be seen from the classical completeness which was achieved by 75% and of the 36 students there were 7 students who had not completed individually, the results of the analysis from the test cycle I. While in cycle 2 the average of all indicators reached 3.9 this was categorized as very high. There was an increase of 0.87 from cycle I this was due to the students being able to adjust. The student learning outcomes in cycle II have increased from the previous cycle. Analysis of daily repetitions in cycle II. These results have increased from the cycle I can be seen from the results of the average value. The average on cycle I was 73.61 and cycle II was 84.03. Meanwhile, classical learning completeness in the first cycle only reached 75%, in the second cycle it had reached the classical completeness standard applied by the school which reached 84.03%. Based on the results of the research it can be shown that the application of the SAVI approach can increase student activity and learning outcomes.